Non invasive tests for diagnosis of parasitic infections of CNS - R S Jayshree; Anita Mahadevan (Wolters Kluwer Medknow Publications, 2022)
Central nervous system (CNS) infections are among the most devastating diseases with high mortality and morbidity. In the pre-human immunodeficiency virus (HIV) era, the occurrence of CNS infections was very infrequent. However, in the past four decades or so, with a global increase in the immunocompromised population, the incidence of opportunistic infections of the CNS has changed. This includes a global increase in the incidence of parasitic infections such as Toxoplasma gondii. Infections such as neurocysticercosis and cerebral malaria are quite prevalent in developing countries. Early diagnosis of these infections is crucial for instituting accurate therapy and preventing mortality and morbidity. Despite advances in neuroimaging techniques, laboratory diagnosis remains the mainstay for confirmation of diagnosis. We present an update on the noninvasive tests available for laboratory diagnosis of parasitic infections of the CNS.